Executive Dysfunction and Reduced Self-Awareness in Patients With Neurological Disorders. A Mini-Review - Amanzio, Martina; Bartoli, Massimo; Cipriani, Giuseppina Elena; Palermo, Sara (Frontiers in Psychology, 2020)
Awareness of deﬁcits in patients with neurological disorders may be described as a theoretical unitary phenomenon, which has been analysed reaching interesting results in the last decades. Awareness of deficits manifests itself in a continuum ranging from full awareness to total absence. In line with a neurocognitive approach, a reduction in self-awareness could be explained considering executive dysfunction associated with prefrontal cortex anatomo-functional changes. Our mini-review will focus on reduced self-awareness in neurological disorders, such as Alzheimer’s disease, behavioural Frontotemporal Dementia and Acquired Brain Injuries. Results achieved thanks to an explanatory investigative approach combined with a theoretical reference model will be presented. Data suggest the key role of executive functions in supporting adequate self-awareness towards patients’ cognitive-behavioural profile and instrumental activity autonomy. The Cognitive Awareness Model seems to be one of the best theoretical model to better approach this phenomenon.